Balinese Muslim Women’s Cultural Identity in the Context of Ajeg Bali - Nabilatum Masruroh; Rosa , Dien Vidia; Prasetyo , Hery (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This research explores the negotiations carried out by Balinese Muslim women in Candikuning and Sinduwati in articulating their religious and cultural identities. The problems that arise in the study are related to stereotypes about being a Balinese Muslim, the origin of the land of birth, and the issue of secularism. Ajeg Bali, as a Balinese regional government regulation, presents a duality of interpretation of religious practices between Islam and Hinduism as social identities; for Balinese Islamic women, religious attributes such as the hijab are limited through the excessive practice of Ajeg Bali. Meanwhile, for those who adhere to Hinduism, religious practices are emphasized as an identity that is demonstrated and integrated into everyday life. Articulating identity through the legitimacy of local authorities strengthens Balinese identity. Yet, it is a challenge that Balinese Muslim women must manage, mainly to minimize cultural conflict. Marvasti’s ethnographic method is used with Fatima Mernissi’s perspective to elaborate on the identity of Islamic women. The research results show Balinese Islamic women’s negotiations are practiced through language and clothing in the Ajeg Bali practice. Then, the authors argue that cultural hybridity is demonstrated through Balinese dance arts and has combined with Islamic and Balinese aesthetics by strengthening the discourse of being Balinese Islamic Women. Hence, Islamic religious practices need to be formulated with the adoption of Balinese culture to enhance and maintain Balinese Islamic identity without neglecting the value of being Muslim.